Analisa Gaya Komunikasi Nessie Nilover Judge dalam Konten Youtube “Kisah “Diktator” Indonesia: Soeharto #Historytelling” di Youtube Channel “Nessie Judge” - Lazar Lira, Muhammad; Syafrudin Syahri, Akhmad (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Nessie Judge is a YouTuber who comes from Indonesia and also has Pakistani descent with content on her YouTube such as the historical story "THE STORY OF THE INDONESIAN 'DICTATOR': SOEHARTO #STORYTELLING", the owner of a YouTube account named Nessie Judge as well as a storyteller who provides information about history on her YouTube account This time the researcher made observations on the communication style carried out by Nessie Judge through analysis units which were classified into several values and aspects of communication style using this qualitative method. Several communication styles and aspects of communication were found, such as The structuring style, Controlling Style, Relinquishing Style and several findings from the communication aspects of Animated Expressive, Friendly, Dramatic, Open, there are also supporting instruments such as music and animated images identified in the video by non-participatory observation through uploading video documentation on Nessie judge's YouTube media.